Synthesis and Crystal Structure of trans-2-(2-Chlorophenyl)-1-nitroethylene - Hao, Er-Jun; Liu, Yun-Feng; Han, Li-Feng; Zhang, Jia-Ling (Asian Journal of Chemistry, 2013)
A nitroalkene compound [trans-2-(2-chlorophenyl)-1-nitroethylene (I)], derived from the condensation of o-chlorobenzaladehyde with nitromethane, has been synthesized and structurally characterized by elemental analysis, 1H NMR spectrum and single-crystal X-ray diffraction analysis. Compound (I) crystallizes in the monoclinic, space group P2(1)/n with a = 4.7364(9), b = 11.908(2), c = 14.914(3) Å, a = 90, b = 91.21(3), g = 90º, V = 841.0(3) Å3, Z = 4, C8H6ClNO2, Mr = 183.59, Dc = 1.450 g/cm3, F(000) = 376, μ(MoKa) = 0.408 mm-1, the final R1 = 0.0550 and wR2 = 0.1430 for 1306 observed reflections [I > 2s(I)]. In addition, X-ray analysis reveals that both the C-Cl···O short contacts and the p-p stacking interactions are observed in the crystal structure. The two kinds of intermolecular interactions extend the molecules into an infinite three-dimensional network.